Seismic Retrofitting Of the 19(TH) Century Hirka-i Serif Mosque Using Textile Reinforced Mortar - Demir, C.; CÖMERT, MUSTAFA; KOÇAK, PINAR İNCİ; Dusak, S.; İlki, A. (Taylor & Francis Inc., 2022)
In this study, a novel retrofitting intervention on the Hirka-i Serif Mosque (constructed in 1851), which has a significant importance for Muslims due to its historical relic preservation unit keeping the cloak of the Prophet Muhammad, was illustrated. For this purpose, first the seismic performance of the mosque was investigated through site investigations and structural analyses. A 3D finite element model of the Mosque was established, and the structural system was analyzed under the combined effects of the vertical loads and seismic actions. Additionally, the existing damages observed on the walls and vaults were investigated thoroughly. By taking the existing damages and the analyses results into consideration, a rehabilitation and seismic retrofit scheme was proposed and applied by making use of innovative materials. Throughout the study, recommendations of the guideline for earthquake risk management of historical structures in Turkey (2017) has been considered.
Keywords: Assessment; FRP Anchors; Masonry; Minaret; Mosque; Retrofit; Seismic; TRM